MBRS-36. IDENTIFICATION OF TWO PROTEIN-SIGNALING STATES DELINEATING TRANSCRIPTIONALLY HETEROGENEOUS HUMAN MEDULLOBLASTOMA. Issue 2 (22nd June 2018) - Zomerman, Walderik; Plasschaert, Sabine; Conroy, Siobhan; Scherpen, Frank; Boer, Tiny Meeuwsen-de; Lourens, Harm-Jan; Llobet, Sergi Guerrero; Smit, Marlinde; Slagter-Menkema, Lorian; Seitz, Annika; Gidding, Corrie; Hulleman, Esther; et al.
Abstract: Medulloblastoma consists of different transcriptional subgroups. To characterize medulloblastoma at the phosphoprotein-signaling level, we performed high-throughput peptide phosphorylation profiling on a cohort of SHH, Group 3 and Group 4 medulloblastomas. We identified two major protein-signaling profiles. One profile was associated with rapid death post-recurrence and resembled MYC-like signaling for which MYC lesions are sufficient but not necessary. The second profile showed DNA damage, apoptotic and neuronal signaling. Integrative analysis demonstrated that heterogeneous transcriptional input converges on these protein-signaling profiles: all SHH and a subset of Group 3 patients exhibited the MYC-like protein-signaling profile, the other Group 3 subset and Group 4 patients displayed the DNA damage/apoptotic/neuronal signaling profile. Functional analysis highlighted cell cycle progression and protein synthesis as therapeutic targets for MYC-like medulloblastoma.